Factors Associated with Violence in School-Age Children in Families in Pasie Nan Tigo Village Koto Tangah District Padang City - Novita Sari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Children are a group that is very vulnerable to violence because they are often considered as weak or helpless individuals. Children who experience violence tend to have strong memories of the harsh treatment carried out by their parents. This paper aims to identify factors related to violence against school-age children in the family environment in Pasie Nan Tigo Village, Koto Tangah District, Padang City. This type of research is a mix-method with a sequential explanatory design. The number of quantitative data samples was 239 respondents using Proportional Stratified Random Sampling and qualitative analysis of 6 participants using purposive sampling. The results of quantitative data obtained the level of parental knowledge (50.2%), secondary education (high school/equivalent) (63.6%), low socio-economic category (59%), sufficient family environment (47.3%) and poor communication patterns (84.5%). Those who experienced violence were 65 respondents (27.2%). There is a significant relationship between knowledge, education, socio-economic and environment with violence against school-age children in the family and no significant relationship between communication patterns and violent behavior in school-age children in the family. The dominant factors related to violence against school-age children in the family are knowledge of 9.673 and socio-economic of 16.057. The health and child protection service should be able to increase their sensitivity to cases of crime against children and participate in reducing the number of cases of violence against children and provide education and counseling to the community regarding violence against children.